Analysis of Utaut Application on Digital Bank Usage in Jabodetabek - Hanifah, Aulianti; Wulandari, Christina Dewi (International Journal of Scientific Research and Management (IJSRM), 2024)
Digital banking is a form of adaptation to new threats and changes in the banking sector. This can be seen from the actions of major banks launching their own digital banks. Such as Digibank, Bank Jago, Jenius and TMRW which were founded by major banks in Indonesia. The purpose of this study is to analyze the effect of UTAUT variables on digital bank users in Jabodetabek. The analysis method used in this research is PLS-SEM with the SmartPLS 3.3.3 application tool. The data obtained in this study were taken using a questionnaire instrument with Google Form. The stages of analysis carried out in this study are starting from the outer model, inner model, and hypothesis testing. The acquisition of valid data that was successfully collected was 250 respondents. The sampling method in this study is non probability sampling with purposive sampling technique. The results of this study indicate that performance expectancy, effort expectancy, and social influence have an influence on behavioral intention and facilitating conditions and behavioral intention also have an influence on use behavior. In this study it was found that only experience can moderate the relationship between facilitating conditions and use behavior.